2022
DOI: 10.3389/fonc.2022.918340
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Exerts Significant Antitumor Effects by Suppressing Vasculogenic Mimicry in Breast Cancer Cells

Abstract: BackgroundNumerous clinical and experimental observations have alluded to the substantial anti-neoplastic role of vitamin D in breast cancer (BC), primarily by inducing apoptosis and affecting metastasis. Tumor progression and resistance to chemotherapy have been linked to vasculogenic mimicry (VM), which represents the endothelial-independent formation of microvascular channels by cancer cells. However, the effect of vitamin D on VM formation in BC has not been thoroughly investigated. This study examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Also, calcitriol exerts potent anti-inflammatory activity, partially through downregulating JAK-STAT pathway activation and inflammatory cytokine production, processes known to be involved in carcinogenesis and VM [ 16 , 17 ]; however, calcitriol’s effects upon VM has not been explored. Regarding this, while this article was under peer review, Khuloud Bajbouj et al, reported that calcitriol differentially downregulated VM-related pathways and the expression of key VM markers in calcitriol-treated breast cancer cells by an in silico analysis of transcriptomic databases [ 18 ]. The same research group also showed that a very high concentration of calcitriol (10 μM) stimulated the expression of tissue inhibitors of MMPs (TIMPs) and decreased that of MMPs, lowering the formation of VM in MDA-MB-231 cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, calcitriol exerts potent anti-inflammatory activity, partially through downregulating JAK-STAT pathway activation and inflammatory cytokine production, processes known to be involved in carcinogenesis and VM [ 16 , 17 ]; however, calcitriol’s effects upon VM has not been explored. Regarding this, while this article was under peer review, Khuloud Bajbouj et al, reported that calcitriol differentially downregulated VM-related pathways and the expression of key VM markers in calcitriol-treated breast cancer cells by an in silico analysis of transcriptomic databases [ 18 ]. The same research group also showed that a very high concentration of calcitriol (10 μM) stimulated the expression of tissue inhibitors of MMPs (TIMPs) and decreased that of MMPs, lowering the formation of VM in MDA-MB-231 cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this, while this article was under peer review, Khuloud Bajbouj et al, reported that calcitriol differentially downregulated VM-related pathways and the expression of key VM markers in calcitriol-treated breast cancer cells by an in silico analysis of transcriptomic databases [ 18 ]. The same research group also showed that a very high concentration of calcitriol (10 μM) stimulated the expression of tissue inhibitors of MMPs (TIMPs) and decreased that of MMPs, lowering the formation of VM in MDA-MB-231 cells [ 18 ]. The effects of curcumin, those of nanomolar calcitriol concentrations, and those exerted by the combination of these compounds on VM development in breast cancer, as well as the mechanisms potentially involved, do, however, remain unknown, which were the originating concepts of our research question.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the function of vitamin D proposed that the metastatic cascade is affected by the vitamin D plasma serum level ( 35 38 ); therefore, we hypothesize that there might be an association between the site and/or presence of metastases and the vitamin D plasma level in germ cell tumor patients. Positive association between low vitamin D level and promotion of bone metastasis as well as lung metastases in mice with breast tumor models was well described ( 36 , 39 ); thus, potential correlation between clinic-pathological variables in testicular germ cell tumor and vitamin D plasma level might be present as well.…”
Section: Introductionmentioning
confidence: 94%
“…EMT can cause tumor cells to lose epithelial markers and acquire mesenchymal characteristics, giving tumor cells phenotypic plasticity, thereby enhance the motility and invasiveness of tumor cells and facilitate VM formation ( Xiao et al, 2023 ). In addition, various cytokines have been identified as contributing to the formation of VM, such as IL6, IL8, IL17, VEGF and TGF-β ( Yang et al, 2016 ; Sharma et al, 2018 ; Bajbouj et al, 2022 ; Hu et al, 2022 ). Most of the them work by activating the biological process of EMT.…”
Section: Introductionmentioning
confidence: 99%